Peningkatan Kemampuan Menulis Karya Ilmiah Siswa SMKN 3 Yogyakarta dengan Metode Galeri Belajar Berbantuan Padlet - Hanidian, Opi; Sudaryanto; Siswanto, Aruji (UPA Bahasa Universitas Tidar And HISKI Kedu, 2023)
The background to writing this article is the low ability to write scientific papers of students in the Indonesian language subject at SMKN 3 Yogyakarta. The application of inappropriate learning models and methods and low student learning motivation result in low student learning outcomes. The purpose of this study was to determine the ability to write scientific papers of students of SMKN 3 Yogyakarta and to find out the results of increasing the ability to write scientific papers of students of SMKN 3 Yogyakarta with the Padlet-assisted learning gallery method. The method used in this study is the learning gallery method (gallery walk) assisted by Padlet media with learning modelsProject Beased Learning (PJBL). The results showed that the Padlet-assisted learning gallery method experienced an increase in cycle 1 of (82%) and in cycle II of (100%) with a target result of (18%). In addition, the observation indicators in cycle I obtained an average increase of (66.4%) and in cycle II (87%). So it can be concluded that the ability to write scientific papers of SMKN 3 Yogyakarta students has increased and the Padlet-assisted learning gallery method can be used as an alternative for learning scientific work in class XI in learning Indonesian.